Komposisi Spesies Capung (Odonata) di Kawasan Cagar Alam Mandor Kecamatan Mandor Kabupaten Landak Kalimantan Barat - Kustiati, Ayu Seftia Nur Wulandari, Tri Rima Setyawati, (Universitas Tanjungpura, 2019)
Dragonfly is one of the predatory insect that can be used as an environmental bio-indicator. Mandor Nature Reserve forest area, which has 3.080 Ha, had changed due to illegal logging and illegal gold mining (PETI) giving a sustainable impact on its flora and fauna. This research aim was to determine the species of dragonfly found in the Mandor Nature Reserve area. The sampling was conducted in one month with the Purposive Random Sampling method. Adult species were collected fortnightly by using sweep nets. There were 182 individuals belonged to 2 suborders, 3 families, 11 genera, and 12 species of dragonflies found in Mandor Nature Reserve area. Two suborders are Zygoptera and Anisoptera, the three families are Coenagrionidae, Gomphidae and Liebellulidae. The most common species found of dragonflies is Cerinorubellum ceriagrion (33 individuals or 18%) and Nannophya pygmaea (29 individuals or 16%), Orthetrum sabina (23 individuals or 13%) andÂ the least common dragonfly is Periagrion microcephallum (4 individuals or 2.16%).